Clinical characteristics of adult patients hospitalized with laboratory-confirmed COVID-19 pneumonia. Issue 2 (February 2021) - Altunok, Elif Sargin; Alkan, Mustafa; Kamat, Sadettin; Demirok, Berna; Satici, Celal; Demirkol, Mustafa Asim; Gursoy, Bengul; Surmeli, Cemile Dilsah; Cengel, Ferhat; Calik, Mustafa; Turkmen, Ulku Aygen
Abstract: Background: The clinical spectrum of COVID-19 has a great variation from asymptomatic infection to acute respiratory distress syndrome and eventually death. The mortality rates vary across the countries probably due to the heterogeneity in study characteristics and patient cohorts as well as treatment strategies. Therefore, we aimed to summarize the clinical characteristics and outcomes of adult patients hospitalized with laboratory-confirmed COVID-19 pneumonia in Istanbul, Turkey. Methods: A total of 722 adult patients with laboratory-confirmed COVID-19 pneumonia were analyzed in this single-center retrospective study between March 15 and May 1, 2020. Results: A total of 722 laboratory-confirmed patients with COVID-19 pneumonia were included in the study. There were 235 (32.5%) elderly patients and 487 (67.5%) non-elderly patients. The most common comorbidities were hypertension (251 [34.8%]), diabetes mellitus (198 [27.4%]), and ischemic heart disease (66 [9.1%]). The most common symptoms were cough (512 [70.9%]), followed by fever (226 [31.3%]), and shortness of breath (201 [27.8%]). Lymphocytopenia was present in 29.7% of the patients, leukopenia in 12.2%, and elevated CRP in 48.8%. By the end of May 20, 648 (89.7%) patients had been discharged and 60 (8.5%) patients had died. According to our study, while our overall mortality rate was 8.5%, this rate was 14.5% in elderly patients, and the difference was significant. Conclusions: This case series provides characteristics and outcomes of sequentially adult patients hospitalized with laboratory-confirmed COVID-19 pneumonia in Turkey.